A Shifting Tide: Recommendations for Incorporating Science Communication into Graduate Training. (November 2016) - Hundey, Elizabeth J.; Olker, Jennifer H.; Carreira, Cátia; Daigle, Rémi M.; Elgin, Ashley K.; Finiguerra, Michael; Gownaris, Natasha J.; Hayes, Nicole; Heffner, Leanna; Roxanna Razavi, N.; Shirey, Patrick D.; Tolar, Bradley B.; et al.
Abstract: Scientists who are skilled in communication reap professional and personal rewards. Unfortunately, gaps exist in fostering curricular and extracurricular training in science communication. We focus our article on opportunities for university‐ and department‐level leadership to train new scientists to communicate effectively. Our motivation is threefold: (1) communication training is key to being competitive in the increasingly diverse job market, (2) training early career scientists in communication "jump‐starts" personal and societal benefits, and (3) the authors represent a group of early career aquatic scientists with unique insights on the state of and need for training. We surveyed early career aquatic scientists about their science communication training experiences. In summary, survey respondents indicated that (1) science communication training is important; (2) graduate students are interested in training that is not currently available to them; (3) departments and advisors are moderately supportive of students participating in science communication, but less enthusiastic about providing training support; and (4) graduate students lack opportunities to put science communication training into practice. We recommend departments and institutions recognize the benefits of science communication training, develop a strategy to support such training, and facilitate individualized approaches to science communication.